2020
DOI: 10.1158/1078-0432.ccr-20-0841
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of High- versus Low-dose Lenalidomide Maintenance Therapy of Multiple Myeloma after Autologous Blood Stem Cell Transplantation

Abstract: For multiple myeloma, high-dose chemotherapy and autologous blood stem-cell transplantation (ASCT) followed by lenalidomide maintenance (LenMT) at 10-15 mg/day is considered standard of care. However, dose reductions due to side effects are common and median LenMT doses achieved over time may remain lower. Dose response during LenMT has never been investigated. Patients and Methods: In a multicenter, randomized, open-label trial, patients with multiple myeloma after ASCT and high-dose lenalidomide consolidatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Typically, patients were recommended to start lenalidomide 2–4 months after ASCT at an initial daily dose of 10–15 mg. The mSMART 3.0 criteria were used for risk stratification based on cytogenetics features on interphase FISH [ 5 , 10 ]. Median follow-up and median duration of maintenance therapy were calculated using the reverse Kaplan–Meier estimator method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, patients were recommended to start lenalidomide 2–4 months after ASCT at an initial daily dose of 10–15 mg. The mSMART 3.0 criteria were used for risk stratification based on cytogenetics features on interphase FISH [ 5 , 10 ]. Median follow-up and median duration of maintenance therapy were calculated using the reverse Kaplan–Meier estimator method.…”
Section: Methodsmentioning
confidence: 99%
“…The current most widely agreed upon frontline treatment strategy for multiple myeloma (MM) involves induction with triplet therapies followed by high-dose chemotherapy and autologous stem-cell transplantation (ASCT) for eligible patients, and then maintenance therapy with or without preceding consolidation. Lenalidomide is the preferred maintenance strategy following ASCT, especially in non-high-risk patients with MM, and multiple randomized studies (e.g., CALGB100104, IFM2005-02, GEMIMA, Myeloma IX, German multicenter study) have demonstrated an improvement in progression-free survival (PFS) with lenalidomide maintenance [ 1 5 ]. Only the CALGB100104 study showed a significant overall survival (OS) improvement with lenalidomide maintenance while an OS benefit was not demonstrated in the other studies; possibly because they were not powered for OS as the primary endpoint [ 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…After excluding duplicate reports for the same trial and trials that did not meet the inclusion criteria, 65 discrete RCTs were identified (Figure 1). The Table highlights characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The LenaMain trial recruited patients from 4 June 2009 to 1 February 2015 in six hospitals in Germany. Details were previously published [17]. Briefly, patients were randomized 1:1 to either receive lenalidomide at a 5 mg (Len-low) or 25 mg (Len-high) maintenance treatment (Len MT) after first-line therapy with autologous stem cell transplant.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
“…The LenaMain trial (NCT00891384) was an investigator-initiated, randomized, openlabel, phase-III trial that randomized patients to either receive lenalidomide at 5 mg (Len low) or 25 mg (Len high) [17]. To date, the LenaMain trial is the only clinical trial to show that a higher dosage of lenalidomide maintenance post-transplant benefits patients by extending the time of remission.…”
Section: Introductionmentioning
confidence: 99%